Association between Tumor Markers and Macro Metals – Calcium and Magnesium - C. Ramalingam2*, S. Swaminathan1, Kasthuri Prakash2 and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract Monoclonal antibodies are used to detect serum antigens associated with malignancies. The tumor markers are most useful for monitoring response to therapy and detecting early relapse. Tumor markers are special molecules released by tumor cells, found in high levels in patients with malignancies. Each tumor marker is organ specific and is elevated in specific type of malignancy and its level in circulating blood provide a clue about the type and severity of the disease. The blood level is very useful for diagnosis, prognosis and to check recurrence after treatment. Experiments were performed to investigate and establish if there are any associations between the principle tumor markers viz CEA (colon caner) , CA125 (ovarian cancer) and CA15.3 (breast cancer) to the diagnostically useful macro-metals Calcium and Magnesium and to suggest if the above two metals need to be analyzed along with the tumor markers for the diagnostic purposes. The study was done with the blood serum sample of suspected or established cancer patients (both men and women). For the samples, biochemical assay using electro-chemiluminescence technique (for CEA, CA 125 and CA 15.3) was used; Calcium and Magnesium were analyzed using manual dye-binding methods and the readings were acquired using a semi auto analyzer. Appropriate statistical methods were used to conclude that, there exists a very strong relationship between CA 125 and CA 15.3; and proved that CA 15.3 is linked to both metals Calcium and Magnesium; whereas CEA shows an inverse correlation with CA 125. 1Head of Biochemistry, Apollo Specialty Hospitals, Chennai; 2School Biosciences and Technology, VIT, Vellore-632001, Tamil Nadu, India Please Cite This Artilce As: S. Swaminathan, Kasthuri Prakash and C. Ramalingam. 2010. Association between Tumor Markers and Macro Metals – Calcium and Magnesium. J. Exp. Sci. 1(4) 14-20.